Application of adenosine 5'-triphosphate (ATP) infusions in palliative home care: design of a randomized clinical trial - van den Borne Ben E; Ars Lisette; Winkens Ron A; van den Beuken Marieke; Spreeuwenberg Cor; Hupperets Pierre S; van Rossum Erik; Beijer Sandra; de Graeff Alexander; Dagnelie Pieter C (BMC, 2007)
Abstract Background Palliative care in cancer aims at alleviating the suffering of patients. A previous study in patients with advanced non-small-cell lung cancer showed that adenosine 5'-triphosphate (ATP) infusions had a favourable effect on fatigue, appetite, body weight, muscle strength, functional status and quality of life. The present study was designed 1. To evaluate whether ATP has favourable effects in terminally ill cancer patients, 2. To evaluate whether ATP infusions may reduce family caregiver burden and reduce the use of professional health care services, and 3. To test the feasibility of application of ATP infusions in a home care setting. Methods/Design The study can be characterized as an open-labelled randomized controlled trial with two parallel groups. The intervention group received usual palliative care, two visits by an experienced dietician for advice, and regular ATP infusions over a period of 8 weeks. The control group received palliative care as usual and dietetic advice, but no ATP. This paper gives a description of the study design, selection of patients, interventions and outcome measures. Discussion From April 2002 through October 2006, a total of 100 patients have been randomized. Follow-up of patients will be completed in December 2006. At the time of writing, five patients are still in follow up. Of the 95 patients who have completed the study, 69 (73%) have completed four weeks of follow-up, and 53 (56%) have completed the full eight-week study period. The first results are expected in 2007.